PERBANDINGAN DAYA ANTIBAKTERI SILER BERBAHAN DASAR RESIN DAN KALSIUM HIDROKSIDA TERHADAP ENTEROCOCCUS FAECALIS - , ASTI TRI FEBRIHAPSARI; , drg. Wignyo Hadriyanto, M.S., Sp. KG (K). ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the important goals of endodontic treatment is comprehensive obturation of root canals. The success of obturation was directly related to the adequate removal of microorganism and their by-product through mechanical root canal instrumentation, antibacterial irrigation, adequate filling of the root canal space and coronal restoration. Antibacterial activity is one of the desirable properties of an ideal sealer. The purpose of this study was to evaluate the antibacterial activity of the new resin-based root canal sealer (RealSeal) and Calsium hydroxide-based root canal sealer (Sealapex). Agar diffusion method was carried out in four plates previously inoculated with Enterococcus faecalis. As base layer 10ml Mueller-Hinton agar was added on each 20mmx100mm petri dishes. Three 6mm diameter and 2mm depth wells were made on each well equally distance using stainless steel cylinder. 0,7ml freshly mixed sealers were placed in prepared wells of Mueller-Hinton agar plates. On each petri dishes, resin-based rootcanal sealer was added in the first well as Group I, Calsium hydroxide-based rootcanal sealer was placed in the second well as Group II and the third well remaind empty as negative control. All plates were incubated for 24 hours at 37ÂºC under anaerobic condition. The diameters of bacterial inhibition zone were measured. Statistical analysis with homogeneity of variance test, Shapiro-Wilk test and Independent sample t-test with the trust level 95% (Î± = 0,05) was applied to the data. The average of the antibacterial activity to Enterocococcus faecalis on group 1 was higher than on group 2. The independent sample t-test proved that there were significant differences between the antibacterial activity of resin-based and Calsium hydroxide-based root canal sealers against Enterococcus faecalis. The conclusion showed that all of the sealers caused bacterial growth inhibition. RealSeal shows superior antibacterial result over Sealapex against Enterococcus faecalis.